2020
DOI: 10.3390/jof6040244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host, Environment and Fungal Growth on Fungal Leaf Endophyte Communities in Taiwan

Abstract: Fungal endophytes inhabit plant tissues without causing disease symptoms. They are highly diverse and distributed globally in all plants that have been investigated. Host, geographic, and environmental effects on endophyte communities have been reported in several studies, but the direct effect of fungal growth rate on endophyte composition has not been tested. To understand the relationship between foliar endophyte composition and fungal growth and to examine the effect of host, elevation, and climatic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A symbiotic imbalance occurs when the net cost of symbiosis exceeds the net benefit (Liu et al, 2018), and in such situations, the mycorrhizal fungi may be considered parasitic to plants (Johnson et al, 1997). This nutrient competition affected the normal growth of plants (Huang, 2020). In addition, the interaction between AMF and inoculum sizes was obvious for all indices, excepting Gs and SP (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A symbiotic imbalance occurs when the net cost of symbiosis exceeds the net benefit (Liu et al, 2018), and in such situations, the mycorrhizal fungi may be considered parasitic to plants (Johnson et al, 1997). This nutrient competition affected the normal growth of plants (Huang, 2020). In addition, the interaction between AMF and inoculum sizes was obvious for all indices, excepting Gs and SP (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can affect the endophytic community of plants, including temperature ( Latz et al, 2021 ), precipitation ( Huang, 2020 ), and soil property ( Lehtonen et al, 2005 ). It has been reported that temporal changes can cause changes in the community composition of the host endophytic bacteria named temporal patterns ( Jackson and Denney, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The final endophyte community assembly of a host plant is a delicate balance between the host, environment, and the fungi that compete with one other. Therefore, it could be predicted that more adaptable and fast-growing fungi are abundant in endophytic communities (although this is yet to be entirely proven), thus increasing the isolation frequency of such fungi [ 167 ]. As a result of all these factors, there is a high chance of slow-growing isolates not being accurately represented in an endophyte community when derived via a solely culture-dependent approach.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…Presumably, these sequences could represent old taxa which have not yet been sequenced. Huang [ 167 ] suggested that we should incorporate sequences generated from NGS and sequences from cultures in introducing novel taxa. However, the ICNafp does not allow us to recognize voucher-less taxa (dark taxa) as accepted species.…”
Section: Towards Sequence-based Nomenclaturementioning
confidence: 99%